2022
DOI: 10.3390/en15145247
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Proxy Modeling Highlighting Applications for Reservoir Engineering

Abstract: Numerical models can be used for many purposes in oil and gas engineering, such as production optimization and forecasting, uncertainty analysis, history matching, and risk assessment. However, subsurface problems are complex and non-linear, and making reliable decisions in reservoir management requires substantial computational effort. Proxy models have gained much attention in recent years. They are advanced non-linear interpolation tables that can approximate complex models and alleviate computational effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 202 publications
0
2
0
Order By: Relevance
“…Based on the results of laboratory studies and the works of various researchers [20][21][22][23][24][25], a number of physical parameters have been identified that most significantly affect the kinetics of phase separation of the water-in-oil emulsion, namely: chemical composition of the deposit emulsion; its dispersed structure and water content; viscosity and temperature of the W/OE; percentage of input and chemical composition of the demulsifier; time of complete water loss (criterion W > 93%); duration of ultrasonic exposure (seconds) and its spectral composition; the hydrodynamic regime of the flow of W/OE; and gas content (Figure 12). In particular, the introduction of a demulsifier affects both the separation of the phases of the emulsion and, by reducing the surface tension, contributes to an increase in the gas output from the W/OE, starting with the degassing stage in the separator.…”
Section: Key Factors Affecting Efficiency W/oe Separation Using a Con...mentioning
confidence: 99%
“…Based on the results of laboratory studies and the works of various researchers [20][21][22][23][24][25], a number of physical parameters have been identified that most significantly affect the kinetics of phase separation of the water-in-oil emulsion, namely: chemical composition of the deposit emulsion; its dispersed structure and water content; viscosity and temperature of the W/OE; percentage of input and chemical composition of the demulsifier; time of complete water loss (criterion W > 93%); duration of ultrasonic exposure (seconds) and its spectral composition; the hydrodynamic regime of the flow of W/OE; and gas content (Figure 12). In particular, the introduction of a demulsifier affects both the separation of the phases of the emulsion and, by reducing the surface tension, contributes to an increase in the gas output from the W/OE, starting with the degassing stage in the separator.…”
Section: Key Factors Affecting Efficiency W/oe Separation Using a Con...mentioning
confidence: 99%
“…Statistics-based models (e.g., response surfaces) provide a function that approximates the response of a full numeric simulator by capturing the input-output relationship of a sample of input parameters [14]. RFMs aim at simplifying the physics of a process, in this case, the fluid flow process inside the reservoir, by applying several hypotheses, while ROMs are used to decrease a primary system's dimensionality by ignoring insignificant parameters while, at the same time, keeping the dominant features and physics over a defined space [14,15]. In the present review, ML-based models are considered in detail thanks to their ability to identify trends and patterns between input variables and the desired outcome and of handling multi-dimensional and multi-variety data.…”
Section: Introduction 1reservoir Simulation In the Oil And Gas Industrymentioning
confidence: 99%